(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Agricultural diversification is an essential strategy, which enhances agricultural income, minimizes risks due to crop failures helps to earn foreign exchange. The most important input required for sustainable agricultural development is irrigation as it facilitates multiple cropping and increase crop productivity. The irrigation brings about overall changes in agriculture. Diversification in agriculture has tremendous impact on the agro-socio-economic impact and uplifting of resources-poor farming communities. It generates income and employment for rural youth. This study was mainly depends on primary data. It was collected from 200 farmers of Radhanagari and Jangamhatti command area and other relevant variables were collected through field work for the year 2013-14. The data have been interpreted in terms of cropping pattern and analyzed by using descriptive statistics and presented by using different kind of graphs. It was concluded that the whole picture of Radhanagari and Jangamhatti irrigation command area has been changed in terms of agricultural diversification after the construction of dam. In fact it help to bring out technological changes in agriculture thereby enhance economic prosperity of farmers and the region. This paper deals with the, cropping pattern, and magnitude of the extent of agricultural diversification that is taking place in both the talukas of Kolhapur district before and after the construction of dams and explore the farmers’ cropping strategy and to identify the determinants of diversification in both talukas.